Are People With Blood Group O More Susceptible to Nasopharyngeal Carcinoma and Have Worse Survival Rates? A Systematic Review and Meta-Analysis - Jing, Shao-wu; Xu, Qing; Zhang, Xin-yuan; Jing, Zhong-hao; Zhao, Zhi-jun; Zhang, Ruo-hui; Wu, Feng-peng; Wang, Jun (Frontiers in Oncology, 2021)
Objective: Nasopharyngeal carcinoma (NPC) is a common malignant tumour in Southeast Asia, especially in southern China. ABO blood groups have been proven to play an important role in many cancers. However, it is still controversial whether the ABO blood group has a definite relationship to susceptibility to NPC and the prognosis of NPC patients. This meta-analysis was performed to elucidate the correlation between ABO blood group and NPC to provide more data for clinical practice. Methods: A systematic search was performed of the Chinese National Knowledge Infrastructure (CNKI), Wanfang, Web of Science, EMBASE, and PubMed databases up to December 31, 2020. Stata 11.0 statistical software was used for this meta-analysis. Results: According to the inclusion and exclusion criteria, a total of 6 studies including 6938 patients with NPC were selected. Blood group O was relevant to Chinese NPC patients, and patients with blood group O had a significantly lower incidence of NPC, while blood group A had no correlation with susceptibility to NPC. There was no difference in the 3-year overall survival (OS), locoregional relapse-free survival (LRRFS) or distant metastasis-free survival (DMFS) rates between patients with blood group O and those with non-O blood groups; worse 5-year OS, LRRFS and DMFS rates were found in patients with blood group O, whereas blood group A was not related to prognosis. Conclusion: Blood group O in Chinese patients with NPC seems to be a protective factor for morbidity. However, once patients with blood group O are diagnosed with NPC, this blood group often indicates unfavourable OS, LRRFS and DMFS rates. It is recommended that more attention should be paid to the influence of blood group factor on patients in the treatment of NPC.